Artificial Intelligence in medicine AIME ’05 - Miksch, Silvia; Hunter, James; Keravnou-Papailiou, Elpida (My University, 2006)
The 10th Conference on Artificial Intelligence in Medicine (AIME '05), held in Aberdeen, Scotland, on 23 27 July 2005, presents papers on the international state of art of artificial intelligence (AI) in medicine (AIM) from both a research and an application perspective. The themes on which papers and the sessions were organized include temporal representation and reasoning, decision support systems, ontology and terminology, case-based reasoning, signal interpretation, visual mining, computer vision and imaging, and knowledge management. The papers deal with the fields of natural language processing, linguistic analysis, and information extraction, and also with guideline based care and how these methods can be utilized to support different tasks in this area. The papers also propose a multi-step approach using information extraction methods to support the human modeler by both automating parts of the modeling process and making the modeling process traceable and comprehensible
Keywords: Artificial intelligence; Medicine; Evidence-based medicine; Linguistics; Medical literature; Semantics